THE FINAL STAGE OF COLLECTIVE FARM CONSTRUCTION IN THE CENTRAL CHERNOZEM REGION IN THE REPORTS OF VKSU STUDENTS ON INDUSTRIAL PRACTICE - Tikhomirov N.V. (Вестник Брянского государственного университета)
The article is devoted to the analysis of the activities of students of the All-Union Communist Agricultural University named after Y.M. Sverdlov during industrial practice in agricultural organizations of the central Chernozem region at the final stage of the socialist restructuring of the village. The work is based on the data of reports prepared by students of the VKSU for the academic part of the university. The source base was made up of documents of the spring practice of 1936. The subject of the study was a complex of relations characterizing the daily life of employees of collective farms, state farms and MTS in the specified historical period. The relevance of the work is due to the low level of study of this range of issues, as well as the author’s appeal to documents that have not previously been involved in solving such problems. For the first time, materials that were not previously in demand in research on the problems of collectivization in the USSR, as well as collective farm everyday life during the second five-year plan, are being introduced into scientific circulation. The information potential of the source makes it possible to study the life of collective farm peasants in everyday, economic, and cultural dimensions. It is shown what role the young specialists played in establishing the work of artels and MTS in the regions of the Russian Black Earth region. The conclusions obtained are intended to expand the source base of scientific research on the problems of socialist transformation of the village in the 1930s, to clarify ideas about the specifics of the creation and functioning of collective farms. The results of the work done serve to deepen the scientific understanding of the processes associated with the restructuring of the village and the place in these processes of students of communist universities of the USSR.